Cervical spine: degenerative conditions - Todd, Andrew G. (Current Science Inc., 2011)
Degenerative cervical spine disorders will affect up to two-thirds of the population in their lifetime. While often benign and episodic in nature, cervical disorders may become debilitating resulting in severe pain and possibly neurologic sequelae. Non-operative treatment continues to play an important role in treating these patients, with medications, therapy and interventional pain injections playing increasing roles in treatment. Surgical treatment including anterior and posterior decompression and fusion have been effective treatments of many cervical disorders, but may lead to significant problems including adjacent level disease. Laminotomy/foraminotomy and total disc arthroplasty may avoid some of these problems while providing similar clinical results. Ongoing clinical trials and studies are helping to define the role of these new technologies in treatment of patients with degenerative cervical disorders, although their greater benefit has yet to be proven.